PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT TERHADAP HASIL BELAJAR SISWA SD - Nurfadilah, Arini; Caturiasari, Jennyta; Nurdiansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is based on the low student learning outcomes and student activities in Civics learning in elementary schools. This research applies the Team Games Tournament type cooperative learning model which aims to improve student learning outcomes and activities through learning which contains elements of tournament games. This research uses the classroom action research (PTK) method which consists of cycle I and cycle II with several stages starting from planning, implementation, observation and reflection. The instruments used in this research were learning evaluation tests, observation of student activities, and interviews. The subjects in this research were class IV students at one of the West Jakarta elementary schools, totaling 30 students. Before implementing the TGT learning model, students obtained learning outcomes of 10%. When implementing the TGT learning model in cycle I, student activity achieved 65% and student learning outcomes achieved 57% with an average of 61.5. This has not achieved the expected target, so the second cycle was carried out with student activities getting 92% and student learning outcomes getting 83% with an average of 75. Based on this, it can be concluded that before implementing the TGT learning model there were still students who experienced understanding. which is low so improvements need to be made for good learning outcomes, then after implementing the TGT learning model, student activities and learning outcomes experience a much better improvement. So, learning by implementing the Team Games Tournament (TGT) model can improve PPKn learning outcomes for grade IV students in elementary schools. Keywords: cooperative learning model type Team Games Tournament (TGT), elementary education, learning outcomes